Physical exercises for preventing injuries among adult male football players: A systematic review - Jorge Pérez-Gómez; José Carmelo Adsuar; Pedro E. Alcaraz; Jorge Carlos-Vivas (Elsevier, 2022)
Background: Football is the most practised sport in the world and is associated with the risk of injuries in the players. Some studies have been published that identify injury prevention programs, but there is no review of the full body of evidence on injury prevention programs for use by football coaches. The aim of this article was to carry out a systematic review of published studies on injury prevention programs for adult male footballers, identify points of common understanding and establish recommendations that should be considered in the design of injury prevention strategies. Methods: PubMed and EMBASE databases were used to identify relevant published articles using the following keywords: "soccer" AND "injury" AND "prevention". Results: A total of 2512 studies were identified initially, but only 11 studies met the inclusion criteria, and their outcomes are presented. Results revealed that injury prevention programs in football have focused on strength training, proprioceptive training, multicomponent programs (balance, core stability, and functional strength and mobility), and warm-up programs. Conclusion: Based on results from the studies analyzed, football players can lower the incidence of match and training injuries by participating in dynamic warm-up programs that include preventive exercises before games or during training sessions, and by adding strength, balance, and mobility training to the training sessions.